PENGEMBANGAN RENCANA PELAKSANAAN PEMBELAJARAN BERBASIS KONTEKSTUAL DI KELAS VIII MTSS NURUL ILMI PADANGSIDIMPUAN - Lili Nur Indah Sari; Abdul Sattar Daulay; Agus Salim Daulay (FORUM PAEDAGOGIK, 2020)
This type of research is a type of RD by applying the ADDIE model (analysis, design, development, implementation and evaluation). This research was conducted at MTsS Nurul Ilmi Padangsidimpuan with 19 students of product trial subjects in class VIII. The data collection instruments used were validation sheets, lesson plans, questionnaires and LAS and used validity and practicality analysis techniques. The results showed that: 1) The lesson plan using a contextual approach was declared very valid with a value of 95, 2) the lesson plan using a contextual approach was stated as very practical with a value of 87. Thus the development of a contextual based lesson plan (lesson plan) on the cubes and blocks, fulfilling aspects of validity and practicality.Â